What makes summer vacation experience memorable? an empirical study from Croatia - Lončarić, Dina; Dlačić, Jasmina; Perišić Prodan, Marina (2018)
This paper aims to examine what kind of experience makes summer vacation memorable and consequently how it influences the overall satisfaction with a vacation experience. Based on literature review hypotheses were formulated in order to explore the multidimensionality of memorable tourist experience, the influence of different elements of memorable tourist experience on satisfaction with tourist vacation as well as the influence of satisfaction with vacation experience on the behavioural intention of tourists. For the purpose of the research, empirical research using paper and pencil questionnaire was carried out on the sample of 134 international tourists who visited traditional sun and sea destinations in Croatia in a broader Kvarner region during the summer of 2017. The research results, although of indicative nature only, point out that a memorable tourist experience consists of four different factors, namely hedonism and novelty, local culture, involvement and refreshment. Among them, local culture has the highest impact on overall satisfaction with summer vacation experience. Also, refreshment as a memorable tourist experience influences the overall vacation satisfaction. The research has also confirmed the positive relationship between the following elements: satisfaction with vacation experience on behavioural intentions that were measured through tourists’ intention to return to the destination, to recommend the destination to their friends and relatives, to share experience through social media and to spend more money in tourist destinations. The strongest relationship is between tourist satisfaction with vacation experience and the intention to recommend a destination followed by intention to revisit that destination if they feel satisfied with the experience provided. Managerial implications as well as limitations and ideas for further research are given.
Svrha rada je istražiti koja vrsta iskustva turista najviše pridonosi nezaboravnom doživljaju ljetnog odmora i posljedično utječe na ukupno zadovoljstvo doživljajem na odmoru. Temeljem pregleda literature razvijene su i predložene hipoteze u cilju istraživanja višedimenzionalnosti nezaboravnog doživljaja turista, istraživanja utjecaja različitih elemenata nezaboravnog doživljaja turista na ukupno zadovoljstvo doživljajem na odmoru, kao i istraživanja povezanosti zadovoljstva doživljajem na odmoru i namjere ponašanja turista u budućnosti. Da bi se postigla svrha istraživanja, provedeno je empirijsko istraživanje pomoću anketnog upitnika koji je proveden na uzorku od 134 inozemna turista koji su tijekom ljeta 2017. godine boravili u tradicionalnim ljetnim destinacijama u Hrvatskoj na širem području Kvarnera, čija se ponuda temelji na moru i suncu. Rezultati istraživanja iako indikativni po svojoj prirodi ukazuju da se nezaboravni doživljaj turista sastoji od četiri različita faktora, odnosno od hedonizma i želje za novotarijama, lokalne kulture, uključenosti i osjećaja osvježenosti. Među njima lokalna kultura ima najveći utjecaj na ukupno zadovoljstvo s doživljajem na odmoru. Istraživanje je također potvrdilo pozitivnu povezanost zadovoljstva s doživljajem na odmoru i namjere ponašanja turista u budućnosti. Namjere ponašanja turista u budućnosti ispitivale su se kroz namjeru povratka u destinaciju, namjeru preporuke posjete destinaciji prijateljima i rođacima, dijeljenje iskustva putem društvenih medija te namjeru da se potroši veći iznos novaca u turističkoj destinaciji. Najsnažnija veza utvrđena je između zadovoljstva turista doživljajem na odmoru i namjere da se preporuči posjet destinaciji. Sljedeća po jačini je povezanost namjere da se ponovi posjet destinaciji ako su turisti zadovoljni doživljajem odmora.
Bibliografija: str. 78-79.
Abstract ; Sažetak.
Keywords: Turisti -- Doživljaji -- Ljetni odmor -- Zadovoljstvo turista -- Namjere ponašanja